(untitled) (Fractal: Journal of Psychology, 2009)
On this article, we start from the assumption that the relation town-madness serves as an analyzer of the deinstitutionalization process in mental health and we seek to indicate the disciplinary and biopolitical borders in operation in this field. For such, we analyze some urban scenes and certain events which we follow in a research about the care practices within a Therapeutic Residential Services (TRS). And, based on the recognition of biopower operation modes in the relation town-madness, we are willing to argue that the resistance forms of biopolitically configured asylums in contemporary should operate macro and micro politically through "struggles in network".